2010
DOI: 10.1007/s12031-010-9383-4
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Islet PACAP Protects Pancreatic β-Cells Against Glucotoxicity and Lipotoxicity

Abstract: Pituitary adenylate cyclase-activating polypeptide (PACAP), a potent insulinotropin, is localized in pancreatic islets. Hyperglycemia and hyperlipidemia impair islet β-cell functions, being recognized as glucotoxicity and lipotoxicity. In this study, we examined whether endogenous PACAP protects islet β-cells against the toxicities. Pancreatic islets were prepared from wild-type and PACAP-null mice, and cultured for 2 days in control conditions containing 5.6 mM glucose, those with elevated 25 mM glucose and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…In the study from Nakata, short-term treatment of islets with palmitate was performed and it was found that the treatment markedly impaired both [Ca 2 + ]i and GSIS in islets of PACAPnull, but not wild-type mice (Nakata et al, 2010). These results indicated that endogenous PACAP in islets played an important role in protecting beta cells against lipotoxicity.…”
Section: Silent Information Regulator 2 Proteinmentioning
confidence: 97%
“…In the study from Nakata, short-term treatment of islets with palmitate was performed and it was found that the treatment markedly impaired both [Ca 2 + ]i and GSIS in islets of PACAPnull, but not wild-type mice (Nakata et al, 2010). These results indicated that endogenous PACAP in islets played an important role in protecting beta cells against lipotoxicity.…”
Section: Silent Information Regulator 2 Proteinmentioning
confidence: 97%
“…Betatrophin mRNA expressions in the liver, WAT and BAT were measured by real-time PCR [17]. Total RNA was isolated using TRIzol (Invitrogen, Carlsbad, CA, USA) and treated with RQ1-DNase (Promega, Madison, WI, USA).…”
Section: Rna Preparation and Real-time Rt-pcr Analysismentioning
confidence: 99%
“…Furthermore, PACAP has also been shown to exert trophic effects on pancreatic ␤-cells (36,37) as in other neuroendocrine cells such as chromaffin cells (38), an effect that may involve SelT. In fact, it has been reported that islets of PACAP-knockout mice are more sensitive to lipo-and glucotoxicity (39). It is thus tempting to speculate that PACAP may protect ␤-cells via SelT up-regulation, which could reduce reactive oxygen species levels and glucotoxicity.…”
Section: Ko Wtmentioning
confidence: 99%